Reliability and validity of generalized anxiety disorder 7-item scale in early pregnant women. Issue 4 (29th November 2022) - Gong, Li-Li; Xie, Xiao-Long; Liu, Si-Tong; Hu, Wei-Hong; Niu, Yu-Jie; Sun, Yi; Liu, Jun-Sheng; Xia, Xian
Abstract : Objective: This study aimed to evaluate the structural reliability and validity of generalized anxiety disorder 7-item (GAD-7) scale in early pregnant women. Methods: In this cross-sectional study, 30, 823 patients in early pregnancy registered in the Obstetrics and Gynecology Hospital of Fudan University completed the GAD-7 scale and patient health questionnaire-9 item (PHQ-9). The discriminative ability, reliability, construct validity, and criterion validity were assessed to evaluate the psychometric properties and factor structures. Items with a discrimination parameter (α) of <0.65, factor loading of <0.30, or cross loading of >0.40 in two or more factors simultaneously were deleted from the scale. Results: All GAD-7 scale items exhibited a high discrimination power. The reliability of the GAD-7 scale was good (Cronbach's alpha coefficient = 0.891). Exploratory factor analysis extracted one factor with eigenvalues of greater than 1.0, which explained 61.930% of the common variance. Confirmatory factor analysis confirmed that the one-factor structure fitted the data well. The correlation coefficient with the PHQ-9 was 0.639. Conclusion: The Chinese version of the GAD-7 scale can be used as a screening tool for early pregnant women. It performs well in terms of discriminative ability, reliability, construct validity, and criterion validity. Pregnant women who screen positive may require more attention and investigation to confirm the presence of generalized anxiety disorder.